HUBUNGAN PERAN TENAGA KESEHATAN, DUKUNGAN SUAMI DAN MEDIA INFORMASI DENGAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT DIWILAYAH KERJA PUSKESMAS SEMBAWA KABUPATEN BANYUASIN - Nunung Suryatini; Eka Afrika; Eka Rahmawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Cancer is one of the leading causes of death in the world. One type of cancer that is often found in women is cervical cancer. Cervical cancer ranks highest in developing countries and ranks 10th in developed countries or ranks 5th globally. One of the reasons for the development of cervical cancer is due to the low coverage of early detection of cervical cancer. The purpose of this study was to determine the relationship between the role of health workers, husband's support and information media simultaneously with the Visual Inspection of Acetic Acid in the working area of ​​the Sembawa Public Health Center, Banyuasin Regency. The type of research used is descriptive analytic research with a cross sectional approach. The research was carried out in the working area of ​​the Sembawaa Public Health Center in July-August 2021 with a sample of 99 respondents. The analysis used is the Chi-square test. The results of the chi-square statistical test showed that value = 0.000 for the variable role of health workers, husband's support variable, and media information was smaller than = 0.05 indicating that there was a significant relationship between the role of health workers and the VIA examination. the relationship between the role of health workers, husband's support and information media on the Visual Inspection of Acetic Acid (IVA) in the Work Area of ​​the Sembawa Health Center, Banyuasin Regency   Keywords             : Visual Inspection of Acetic Acid, the role of health workers, husband's support, media information